Analisis Kepuasan Mahasiswa Terhadap Pelayanan Perpustakaan (Studi Kasus Perpustakaan TI ISTN) - erika erika erika (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
Abstract The success rate of service companies can be measured by how much the level of customer satisfaction with the services provided. Satisfaction is a gap between customer perceptions and expectations. The library is one of the vital service providers in the world of education, as is the ISTN Industrial Engineering Library. In this study the focus of the analysis is on the book lending facilities provided to students. To see the service quality system in the library system the service quality dimension is used in the "Assessment of Library Service Quality", as well as by using the Service Quality Dimension from Bery & Parasuraman. The gap calculation shows that all dimensions are negative, which means customer perceptions are not in line with their expectations. However, from the average plot dimension in the two-dimensional diagram, it was found that there are 7 variables entered in quadrant 3, which means that ISTN IT students are satisfied with library services. Keyword : Library, Assessment of Library Service Quality, Bery & Parasuraman Service Quality Dimensions